Efficient UWB low noise amplifier with high out of band interference cancellation. Issue 1 (1st January 2017) - Taibi, Abdelkader; Trabelsi, Mohamed; Slimane, Abdelhalim; Saadi, Abdelhalim A.; Belaroussi, Mohand Tahar
Abstract : This work provides a new co‐design methodology of ultrawide band (UWB) low‐noise amplifier (LNA) with high out of band interference cancellation. The solution consists to cascade a selective microstrip UWB bandpass filter (BPF) with the proposed 0.18 µm complementary metal–oxide–semiconductor‐based LNA. Indeed, the usefulness of this co‐design technique is to address the interference mitigation through the BPF and amplification function by using the LNA. The proposed solution remains powerful since the out of band interferences are well avoided with an efficient amplification performance while well fulfilling UWB requirements, i.e. good matching over a wide bandwidth from 3.2 to 10.64 GHz, 17 dB of power gain ( S 21 ), the noise figure varies between 2.5 and 5.7 dB, and the dissipated power ( P DC ) is typically 16.5 mW. It is relevant to point out that the computed figure‐of‐merit of the proposed circuit is 29.03 which is very competitive compared with state‐of‐the art.